Updated pharmacoeconomic analysis of atesolizumab efficiency compared with other PD-1 inhibitors in patients with advanced non-small cell lung cancer after chemotherapy - S. K. Zyryanov; I. N. Dyakov (Фармакоэкономика)
Objective: to evaluate the pharmacoeconomic efficiency of atezolizumab (inhibitor of programmed death ligand 1 (PD-L1)) in comparison with other checkpoint inhibitors (inhibitors of programmed cell death protein 1 (PD-1)) in patients with advanced non-small cell lung cancer (NSCLC) after previous chemotherapy in the current conditions of the Russian healthcare system.Material and methods. The study design was a retrospective analysis of publications and modeling. The previously performed pharmacoeconomic study was updated considering a decrease in the cost of pembrolizumab after the generic form was released on the market and actualization of calculated target population. Cost minimization analysis was carried out and the impact on the healthcare system budget was estimated when treating all NSCLC patients provided with PD-1/ PD-L1 inhibitors in the second and third lines of therapy with atezolizumab. For calculations, we used registered prices according to the state register of maximum selling prices and average weighted marginal wholesale markup according to the Federal Antimonopoly Service.Results. In the cost minimization analysis, atezolizumab showed greater clinical and economic efficiency, its use reduces costs by 28.6% over 3 years compared to nivolumab and by 8.8% compared to pembrolizumab in the second and third lines of NSCLC therapy. The budget impact analysis demonstrated that if all patients in the target group currently receiving various PD-1/PD-L1 inhibitors in the second and third lines of NSCLC therapy were initially provided with atezolizumab, it would reduce the budget load over 3 years by 11.6%, or by 722.4 mln rubles.Conclusion. The use of atezolizumab is pharmacoeconomically justified and feasible compared to nivolumab and pembrolizumab, even after a release of the generic version of the latter, and will reduce the costs of PD-1/PD-L1 inhibitors in the second and third lines of NSCLC therapy.